Nursing Students' Satisfaction with Blended Learning in Certain Palestinian Nursing Schools Amidst the COVID-19 Epidemic - Asmar, Imad; Almahmoud, Omar (International Journal of Practice-based Learning in Health and Social Care, 2025)
Students' theoretical and clinical learning is greatly impacted by blended learning in general, and nursing students specifically. This study aims to evaluate nursing students' perceptions of blended learning in the context of the COVID-19 pandemic. An electronic survey questionnaire surveyed 300 undergraduate nursing students from five nursing schools in Palestine. According to the study's findings, 71% of students thought that blended learning was helpful. With a mean of 2.92, the management domain was the highest, while the interaction domain had the lowest mean (M = 2.78). The study found statistically significant differences between academic level (P value = 0.039), academic accomplishment (P <0.001), and other characteristics that were associated with student satisfaction with blended learning. As part of a blended education system's quick transition to remote electronic learning, most undergraduate nursing students questioned for this study expressed satisfaction with their educational experiences.